Reliability-based DG location using Monte-Carlo simulation technique - Mohd Ikhwan, Muhammad Ridzuan; Nur Nabihah Rusyda, Roslan; Noorfatin Farhanie, Mohd Fauzi; Muhammad Adib Zufar, Rusli (Springer Nature Switzerland, 2020)
Reliability targets have become essential to distribution network operator since Energy Regulator set minimum targets of reliability performance of the network and penalise if the targets not achieved. Thus, placement of distributed generation (DG) into network offers improvement in reliability performance. Typically, less attention is given to DG reliability-based placement compared to voltage- and loss-based placement. Therefore, this paper presents the placement of DG based on reliability performance, which applied to medium voltage (MV) and low voltage (LV) sub-urban distribution network. The typical Monte-Carlo simulation technique is used to assess both system and customer-related reliability performance. The placement of DG into MV and LV networks show improvement in terms of reliability performance.